Birth Order and Maternal Age for Reported Cases of Severe Prenatal Cortical Hyperostosis (Caffey-Silverman Disease) - Rolf R. Engel; Raul F. Cifuentes (Thieme Medical Publishers, Inc., 2017)
The spectrum of prenatal cortical hyperostosis includes a mild phenotype that typically presents after 35 weeks of gestation, and a severe form that presents earlier. The skeletal and systemic manifestations of the severe phenotype remain unexplained. A review of reported cases indicates that older mothers and firstborn infants are overrepresented. This combination suggests decreased fertility. Fourteen years after the birth of the present case, his mother presented with renal failure from multiple myeloma raising the possibility that a maternal antibody may play a role in the etiology of severe prenatal Caffey disease. The present case report is also intended to alert clinicians to potential difficulties with tracheal intubation secondary to micrognathia from mandibular involvement during a critical growth period.